Phosphonate‐Type Pseudo‐Grafted Precursor: Efficient Surface Modification of Silica. Issue 4 (22nd November 2021) - Ishizaka, Yusuke; Matsumoto, Kazuhiro; Sato, Kazuhiko; Choi, Jun‐Chul
Abstract: Surface modification of inorganic metal oxides by grafting phosphonate compounds is a highly useful method for acquiring organic–inorganic hybrid materials. Compared to metal oxides, it is still difficult to modify silica by phosphonates. In this work, we developed an arylphosphonate "pseudo‐grafted precursor" ( P ‐PGP 1 ) bearing a disilicate moiety (−OSi(O t Bu)2 OSi(O t Bu)2 O−). While conventional grafting methods rely on Si−O−P bond formation, P ‐PGP 1 undergoes Si−O−Si bond formation through a substitution reaction on the silicon atoms of the disilicate moiety. Therefore, P ‐PGP 1 was grafted onto a silica surface at room temperature with a higher phosphorus content than that obtained with arylphosphonic acid. The characterization of surface species by 31 P and 13 C CP/MAS NMR analyses and the evaluation of the phosphorus content suggested that the grafting mode of P ‐PGP 1 allows efficient surface modification of the silica surface. Abstract : A phosphonate precursor bearing a bidentate disilicate moiety, −OSi(O t Bu)2 OSi(O t Bu)2 O−, was synthesized as a "pseudo‐grafted precursor" (PGP) to effectively modify silica surfaces. The PGP was grafted onto the silica surface with a higher phosphorus content than the corresponding phosphonic acid using a substitution reaction at the silicon atoms of the PGP.